A phase I, open-label study evaluating the safety and pharmacokinetics of trifluridine/tipiracil in patients with advanced solid tumors and varying degrees of renal impairment - Saif, Muhammad Wasif; Becerra, Carlos R; Fakih, Marwan G; Sun, Weijing; Popovic, Lazar; Krishnamurthi, Smitha; George, Thomas J; Rudek, Michelle A; Shepard, Dale R; Skopek, Jiri; Sramek, Vladimir; Zaric, Bojan; et al. (Cancer chemotherapy and pharmacology, 2021)
PURPOSE: Trifluridine/tipiracil (FTD/TPI) is approved for advanced colorectal and gastric/gastroesophageal cancer; however, data in patients with renal impairment (RI) are limited. This phase I study evaluated FTD/TPI in patients with advanced solid tumors and varying degrees of RI to develop dosing guidance. METHODS: Patients were enrolled into normal renal function (CrCl ≥ 90 mL/min), mild RI (CrCl 60-89 mL/min), or moderate RI (CrCl 30-59 mL/min) cohorts and administered the recommended FTD/TPI dose (35 mg/m2 twice daily, days 1-5 and 8-12; 28-day cycle). Based on interim pharmacokinetics/safety data, patients with severe RI (CrCl 15-29 mL/min) were enrolled and received FTD/TPI 20 mg/m2 twice daily. RESULTS: Forty-three patients (normal renal function [n = 12]; mild RI [n = 12]; moderate RI [n = 11]; severe RI [n = 8]) were enrolled and treated. At steady state, compared to values in patients with normal renal function, FTD area under the curve (AUC) was not significantly different in patients with RI, but TPI AUC was significantly higher and increased with RI severity. FTD/TPI safety profile was consistent with prior experience, but grade ≥ 3 adverse events (AEs) were more frequent in the RI cohorts (83.3% [mild], 90.9% [moderate], 75.0% [severe], and normal [50.0%]). Hematologic AEs (anemia and neutropenia) were more frequent with RI. Overall, seven patients discontinued because of unrelated, nonhematologic AEs. CONCLUSION: FTD/TPI is safe and tolerable at the recommended 35 mg/m2 dose in patients with mild/moderate RI and at the reduced 20 mg/m2 dose in patients with severe RI. TRIAL REGISTRATION: NCT02301117, registration date: November 21, 2014.
Keywords: nemoci ledvin; dospělí; Trifluridine/tipiracil; Female; Trifluridine; Safety; Neutropenia; Anemia; Adult; fixní kombinace léků; ženské pohlaví; pyrrolidiny; Neoplasms; nádory; lidé; Pyrrolidines; Pharmacokinetics; neutropenie; Aged, 80 and over; Antineoplastic Combined Chemotherapy Protocols; Kidney Diseases; stupeň závažnosti nemoci; Thymine; protokoly protinádorové kombinované chemoterapie; kohortové studie; Humans; Cohort Studies; trifluridin; Male; Aged; Renal impairment; thymin; lidé středního věku; plocha pod křivkou; senioři nad 80 let; senioři; anemie; mužské pohlaví; Severity of Illness Index; TAS-102; Middle Aged; Drug Combinations; Area Under Curve